Evaluating school efficiency using data envelopment analysis /Paul Lau Ngee Kiong … [et al.] - Paul, Lau Ngee Kiong; Leong, Siow Hoo; Hwa, Tee Yong; Mahdi, Rasidah (2004)
This report presents the findings of a research project, which examined the determinants contributing to school efficiency based on the ‘High Standard Quality Education' framework compiled by the Malaysian School Inspectorate and the new relative efficiencies of the secondary schools in the Sri Aman/Betong Division for the year 2002.